KANDUNGAN LOGAM BERAT TIMBAL (Pb) PADA AIR, SEDIMEN, DAN KERANG DARAH (Anadara granosa) DI PANTAI BELAWAN, PROVINSI SUMATERA UTARA (The contents of lead in Water, Sediment, and Blood Cockle on the Beach in Belawan, North Sumatra province) - Aryalan Ginting; Pindi Patana; Nurmatias Nurmatias (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Metals and the other minerals are commonly found in fresh water and sea water, although the amount is very limited. The heavy metals which come into the waters will pollute the sea. One suspected of marine life will be affected due to degradation of water and sediment in coastal environments is shellfish. The aims of this study are to calculate the number of lead concentrations in the water, sediment, and blood cockle (Anadara Granosa) and to analyzed the correlation between lead consentration in water, sediment, and shellfish.This study was conducted in June-August 2013 in Belawan Beach, Bagan Deli Village, District of Medan Belawan, North Sumatra Province. The number of point stations observed were three stations. Parameters measured were water physico-chemical parameters and the concentrations of lead in the water column, sediment, and blood cockle then analyzed by using atomic absorption spectrophotometer (AAS).The results of research on water showed the lead concentration is about 0.64 to 0.91 mg / L. while lead concentration in sediments ranged from 60.78 to 71.56 and lead concentration in mussels is abut 10.48 to 12.03 mg / kg. These results indicate that water, sediment, and shellfish have been contaminated by lead in Belawan Beach.Keywords : Blood cockle, Heavy metals , Lead.